2018
DOI: 10.1007/s00192-018-3638-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing postoperative voiding dysfunction after mid-urethral sling using either a Babcock or Kelly clamp tensioning technique

Abstract: The Babcock and Kelly clamp tensioning techniques appear comparable, with a low incidence of prolonged postoperative catheterization. Most catheters were removed on the day of the surgery. It is reasonable to tension retropubic midurethral slings with either method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The prevalence of UI increased from 12.0% for men aged 70–74 years old to 16.3% for those aged 90 years and older [ 3 ]. The incidence of UI in post-menopausal and middle-aged women ranges from 44 to 57% [ 4 ]. UI is generally experienced as shameful and repulsive, making it challenging for people experiencing UI to seek health care services [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of UI increased from 12.0% for men aged 70–74 years old to 16.3% for those aged 90 years and older [ 3 ]. The incidence of UI in post-menopausal and middle-aged women ranges from 44 to 57% [ 4 ]. UI is generally experienced as shameful and repulsive, making it challenging for people experiencing UI to seek health care services [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ranges from 44 to 57% [4]. UI is generally experienced as shameful and repulsive, making it challenging for people experiencing UI to seek health care services [5].…”
mentioning
confidence: 99%
“…An RCT of women undergoing retropubic MUS compared tensioning with a Babcock grasping a 1.4-cm loop of mesh versus using a Mayo scissor as a spacer and demonstrated that the Babcock led to lower rates of POUR but resulted in higher rates of mesh extrusion 50 . In contrast, an earlier retrospective study of retropubic MUS tensioning compared a Babcock grasping 0.6 cm of mesh to using a Kelly clamp as a spacer and did not demonstrate a significant difference in the VT pass rate 128 …”
Section: Discussionmentioning
confidence: 95%
“…50 In contrast, an earlier retrospective study of retropubic MUS tensioning compared a Babcock grasping 0.6 cm of mesh to using a Kelly clamp as a spacer and did not demonstrate a significant difference in the VT pass rate. 128 Indwelling catheters are routinely inserted at the time of PRS to prevent intraoperative, overdistention of the bladder typically defined as bladder volumes greater than 400-600 mL. [51][52][53] To our knowledge, there have been no prospective studies investigating the incidence of POUR as it relates to intraoperative bladder drainage versus no drainage in patients undergoing surgery for POP and SUI.…”
Section: Postoperative Urinary Retentionmentioning
confidence: 99%
“…However, very little evidence exists that examines how the intraoperative technique used to determine the amount of space between the midurethral sling and the urethra, also known as setting the mesh tension, 7 affects surgical outcomes. 8 , 9 Furthermore, many of the randomized controlled trials (RCTs) reporting outcomes after midurethral sling procedures do not elaborate on what tensioning mechanism was used, despite existence of many techniques. 10 , 11 …”
mentioning
confidence: 99%